APPLICATION OF GRAPHIC DESIGN PRINCIPLES IN THE DEVELOPMENT OF THE USER INTERFACE OF THE CAR INSTRUMENT PANEL - Куценко, А. В.; Колосніченко, О. В. (Art and Design, 2023)
The purpose of the study is to analyze the means of creating a car dashboard interface. The influence of graphic design on the interface and its integration with information technologies is studied. Methodology. The work uses a historiographical analysis and a visual-analytical method based on car dashboard interfaces to investigate artistic and compositional features in the design of vehicle interfaces. The results. The article is devoted to a comprehensive study of the car dashboard interface, with special attention paid to the principles of graphic design. The types of operating systems that form the basis of the car dashboard interface are considered. On the basis of the standards approved by Google and Apple corporations, common and distinctive features in dashboard interfaces have been identified. The main content of the study is the analysis of dashboard interfaces of well-known car brands. The key stages of the development of the car dashboard interface are considered. The influence of graphic design on the interface of the dashboard of the car was revealed, using the principles of composition, form formation, color science and typography. The scientific novelty consists in revealing the basic principles of graphic design in the development of the car dashboard interface. Based on the study of the research results of D. Norman and J. Nielsen, A. Cooper, D. Raskin, P. Morvil and H. Krishna, the definition of the concept of interface and the importance of its interaction with users has been established. Practical significance. The results of the work make it possible to consider the design of interfaces as a promising direction of graphic design and its integration with information technologies.